Bridging Gender Gap in Physics Classrooms: Do Teaching Approaches Matters? - Afolabi, Folashade; Olajuyigbe, Olufemi A. (NIU Journal of Social Sciences; Vol 4 No 2 (2018): KIU Journal of Social Sciences, Vol. 4 No. 2, June 2018, 2018)
Gender issues in Nigeria have become an issue of concern in the past few years. As schools and educational institutions become more structured, sex differences in education and academic achievement assume new and more focus of researchers. It is quite obvious that despite government effort in achieving gender equity in all sectors of the economy, gender inequality still persist in achievement and enrolment in physics classroom. This has been attributed to the teachers’ factor i.e the teacher and her/his methods of teaching physics concept. Therefore, this study investigated to what extent can constructivist instructional strategies bridged gender gap in physics classroom. The study adopted a quasi-experimental research design with 194 SSII physics students as participants. Physics Achievement Test (PAT) was used for data collection with reliability coefficient of 0.76. It was discovered from the analysis that using appropriate teaching approaches helped female students to learn and remember facts, apply skills, comprehend concepts, analyses and synthesises principles which are cognitive objectives of physics education. Recommendations and suggestions were proffered. Key words: Gender Disparity, Action learning strategy, inquiry-based strategy, conventional strategy, Physics